2011
DOI: 10.1210/en.2010-0456
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Osteogenic and Immunological Effects by the Selective Glucocorticoid Receptor Agonist, Compound A, in Human Bone Marrow Stromal Cells

Abstract: Glucocorticoids (GCs) regulate various physiological processes, including bone remodeling. Whereas physiological amounts of GCs are required for proper human osteoblast differentiation, prolonged exposure to GCs leads to substantial bone loss in vivo predominantly by inhibiting osteoblast functions. Compound A (CpdA) is a novel GC receptor modulator with the potential of an improved benefit/risk profile. Here we tested the osteoimmunological effects of CpdA on primary human osteoblasts and their paracrine inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 27 publications
5
35
1
3
Order By: Relevance
“…The fact that a previous report in intestinal Caco-2 cell line showed no effect of CpdA on MKP-1 expression (35) suggests that the cellular effects of CpdA are highly cell specific. Indeed, we also failed to see any GRa nuclear translocation after CpdA treatment (Figure 4), contrasting with studies (mostly from De Bosscher and collaborators) that reported GRa nuclear translocation after CpdA treatment in different cell types (17,18,28,35,38). The reasons for this discrepancy are not known, but GRa activation by CpdA appears to be highly diverse with profound differences in the kinetic of GRa nuclear translocation (seen at 30 min and at 3-6 h) and CpdA potency (concentrations from 10 nM and up to 20 mM).…”
Section: Discussioncontrasting
confidence: 99%
“…The fact that a previous report in intestinal Caco-2 cell line showed no effect of CpdA on MKP-1 expression (35) suggests that the cellular effects of CpdA are highly cell specific. Indeed, we also failed to see any GRa nuclear translocation after CpdA treatment (Figure 4), contrasting with studies (mostly from De Bosscher and collaborators) that reported GRa nuclear translocation after CpdA treatment in different cell types (17,18,28,35,38). The reasons for this discrepancy are not known, but GRa activation by CpdA appears to be highly diverse with profound differences in the kinetic of GRa nuclear translocation (seen at 30 min and at 3-6 h) and CpdA potency (concentrations from 10 nM and up to 20 mM).…”
Section: Discussioncontrasting
confidence: 99%
“…However, none of these studies examined its effects on bone. In our previous work, we have reported on the bonesparing potential of CpdA in vitro and in vivo (9,21,25), showing that CpdA maintains bone mass in a model of GC-induced bone loss because it does not interfere with bone formation or resorption (21).…”
Section: Discussionmentioning
confidence: 99%
“…None of these studies, however, have addressed the effects of CpdA on the skeleton. In initial studies on bone cells, CpdA, in contrast to conventional GCs, did not increase the receptor activator of NF-B ligand to osteoprotegerin ratio or stimulate osteoclastogenesis in vitro (9). Furthermore, no suppressive effects of osteoblast function were found (9,25).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Osteoblast mineralisation Primary human bone marrow stromal cells (BMSCs) were kindly provided by the Department of Medicine I of the Dresden University Medical Center and cultured according to previously reported methods [28]. BMSCs were maintained in DMEM, 10% fetal calf serum (Supreme, Lonza, Cologne, Germany) and 1% penicillin/streptomycin in a humidified atmosphere of 95% air and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%